Nitrogen enhances diversity of arbuscular mycorrhizal fungi while phosphorus drives community composition in maize rhizosphere after 19 years of fertilization - Gaset, Braian; Rubio, Gerardo; Ferrari, Manuel Carlos; Cavigliasso, Pablo; Nishinakamasu, Veronica; Puebla, Andrea Fabiana; Faggioli, Valeria Soledad (Springer Nature, 2025)
Background and aims: Nitrogen (N) and phosphorus (P) fertilisers are widely used in agro-ecosystems but can endanger the diversity of beneficial soil-borne biota. This study aimed to determine the impact of long-term N and P fertilisation on arbuscular mycorrhizal fungi (AMF), a group of symbiotic soil fungi, by distinguishing between the effects of individual and combined nutrient applications. Methods: We examined the impacts of long-term (i.e. 19 years) N and P fertilisation at two developmental crop stages: V6 (six fully expanded leaves) and R1 (initiation of flowering, after N addition). We measured mycorrhizal colonisation to test the plant-AMF relationship and used Illumina MiSeq sequencing of 18S rRNA gene from rhizospheric soil to evaluate AMF diversity. Results: N and P fertilisation resulted primarily in additive effects rather than interactive effects. N fertilisation greatly increased alpha diversity (e.g. + 38% Chao2 at R1 sampling time) and changed AMF community composition (presence-absence data at R1). P fertilisation reduced mycorrhizal colonisation (~—8% at V6,—21% at R1), changed community composition (relative abundance data at V6 and R1) and negatively affected the abundance and richness of the predominant family Glomeraceae. Conclusions: Long-term additions of N and P change AMF communities in distinct ways. While N mainly contributes to increases in alpha diversity, P influences the assembly of AMF by altering the dominance of major taxa within the community. Future studies are needed to disentangle the implications of these changes for crop yields and nutrient use efficiency to ensure the sustainability of agro-ecosystems.